Aspirations for Growth, Innovation, and Internationalization of the Early-stage Entrepreneurs - Močnik, Dijana; Širec, Karin (Naše gospodarstvo/Our economy, 2014)
In this paper, we empirically assess the relationship between early-stage entrepre- neurial firms’ growth aspirations and their innovative and international orientation. We obtained the data before the economic crisis from the 2003—2008 Global En- trepreneurship Monitor Adult Population Survey for eight southeastern European co- untries (SeEC) and five western European countries (WEC). The results show that a firm’s newness of its technologies used and its offer and international orientations inhibit growth aspirations. In the early stage, firms lack the resources, experience, skills, and networking necessary to grow. The extent of the negative relationships between growth aspirations and innovative and international orientation is bigger in WEC than in SeEC.